Gasto público en salud y muertes por suicidio en América Latina (Tema Central) - Vargas Granja, Sofía Anahí (2026)
Suicide is a phenomenon that has increased in magnitude and relevance in recent decades. The World Health Organization reports that this problem causes 703,000 deaths worldwide each year. This article analyzes the correlation between public health expenditure and suicide rates in 18 Latin American countries: Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Guatemala, Honduras, Jamaica, Mexico, Nicaragua, Panama, Paraguay, Peru, the Dominican Republic, and Uruguay, between 2000 and 2019. Using the generalized least squares (GLS) method, it was found that a 1 percentage point increase in the ratio of public health expenditure to GDP is associated with a decrease of 39 suicides per 100,000 people in the following year. The study highlights the importance of allocating resources to promote mental health, especially in prevention, promotion, and intervention programs with a multisectoral approach that focus on influencing favorable determinants of society’s health and early detection of people at higher risk of suicide.